Market Study for Vietnam : Plastics Circularity Opportunities and Barriers - World Bank Group (World Bank, Washington, DC, 2021)
Vietnam's public and private sector stakeholders are increasingly active in addressing plastics waste. The Vietnam Government has set ambitious national plastics waste management goals to combat the economic and environmental consequences of mismanaged plastics waste nationally. This study uses a plastics value chain approach to evaluate Vietnam’s plastics recycling industry and its role in supporting a circular economy.